Genetic and epigenetic profiling of a solitary Peutz-Jeghers colon polyp - Linhart, Heinz; Bormann, Felix; Hutter, Barbara; Lyko, Frank (Cold Spring Harbor molecular case studies, 2017)
Colon polyps represent precursor lesions of colon cancers and their malignant potential varies according to histological subtype. A rare subtype of colon polyps is the Peutz-Jeghers (PJ) polyp. PJ polyps mostly occur in the context of Peutz-Jeghers syndrome, which is characterized by the development of multiple polyps in the intestinal tract and hyperpigmentation of oral mucosa and lips. Peutz-Jeghers is an autosomal dominant disorder caused by pathogenic variants of the serine threonine kinase STK11. PJ polyps very rarely occur outside of the syndrome and are then referred to as solitary PJ polyps. Contrary to the situation in Peutz-Jeghers, the genetic basis and the malignant potential of solitary PJ polyps are currently unknown. Here we describe a detailed and comprehensive genetic profile of a solitary PJ polyp. Pathological examination revealed a high tissue homogeneity with >80% epithelial cells. Whole-genome sequencing failed to identify any clonal mutations but demonstrated a significant number of subclonal mutations. No somatic or germline mutations were found at the STK11 locus, suggesting that solitary PJ polyps are genetically distinct from Peutz-Jeghers polyps. In addition, methylome analysis revealed global hypomethylation and CpG island hypermethylation, two features that have been described as hallmarks of the colorectal cancer epigenome. These results provide an example of a premalignant lesion that is defined by epigenetic, rather than genetic changes. Furthermore, our findings support the notion that solitary PJ polyps constitute neoplastic tissue with malignant potential that should be removed for cancer prevention.